Let A B C be an isosceles triangle with A B = A C and let I be it's incentre, suppose B C = A B + A I ,find ∠ B A C (in degrees).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I disagree with the stated motivation of "Since we have been asked to find the value of an angle we will focus on angles and not sides." Sometimes finding the (ratio of) sides can make it easier to calculate the angles.
@Calvin Lin i forgot to click on that button yet again.So sorry sir.If convenient could you please provide feedback?
Log in to reply
Below the motivation BC /Sin A= AB/Sin C. Should come
Sir,i have mentioned that as here that seemed like the only way possible.
a Class ! !
Since Δ A B C is isosceles , ∠ B = ∠ C ⇒ π = ∠ A + 2 ∠ C ⇒ ∠ C = 2 π − A .
We know that B C = 2 R sin A , A B = 2 R sin C , A I = 4 R sin 2 B sin 2 C . Thus , by given condition ,
⇒ 2 R sin A = 2 R sin C + 4 R sin 2 B sin 2 C ⇒ sin A = sin C + 2 sin 2 2 C ⇒ sin A = sin ( 2 π − A ) + sin 2 ( 4 π − A ) ⇒ sin A = sin ( 2 π − 2 A ) + sin 2 ( 4 π − A ) ⇒ − sin 2 ( 4 π − A ) = cos 2 A − sin A ⇒ 1 − sin 2 ( 4 π − A ) = 1 + cos 2 A − sin A ⇒ cos ( 2 π − A ) = 1 + cos 2 A − 2 sin 2 A cos 2 A ⇒ sin 2 A = 1 + cos 2 A − 2 sin 2 A cos 2 A ⇒ sin 2 A − cos 2 A + 2 sin 2 A cos 2 A = 1 ⇒ sin 2 A − cos 2 A + 2 sin 2 A cos 2 A = sin 2 2 A + cos 2 2 A ⇒ sin 2 A − cos 2 A = ( sin 2 A − cos 2 A ) 2 ⇒ ( sin 2 A − cos 2 A ) ( sin 2 A − cos 2 A − 1 ) = 0
Case 1:
sin 2 A − cos 2 A = 1 ⇒ ( sin 2 A − cos 2 A ) 2 = 1 ⇒ 1 − 2 sin 2 A sin 2 A = 1 ⇒ sin A = 0 ⇒ A = 1 8 0 ∘ n ∀ n ∈ Z
This case must be discarded since , there is no solution in 0 ∘ < A < 1 8 0 ∘
Case 2:
sin 2 A − cos 2 A = 0 ⇒ sin 2 A = cos 2 A ⇒ 2 A = 4 5 ∘ ⇒ A = 9 0 ∘ ∵ 0 ∘ < A < 1 8 0 ∘
Considering all the cases we have ∠ A = ∠ B A C = 9 0 ∘
Good way of converting the equation into trigonometry and then pushing through the equations.
Let M the midpoint of BC. Then, AI/IM =2c/a (Angle Bisector Theorem) or AI/AM=2c/(a+2c). But AM=√(c²-a²/4); hence, AI=(√(c²-a²/4))(2c)/(a+2c) or AI= a -c =(√(c²-a²/4))(2c)/(a+2c) which simplifies to a²=2c². But b=c, hence a²=b²+c² or tr. ABC is a rt. angled triangle with angle A=90°
S i n c e w e a r e a s k e d f o r t h e a n g l e n o t t h e s i d e s , W L O G , l e t A B = A C = 1 , A I = x T h e n , l e t t h e i n s c r i b e d c i r c l e c e n t r e d a t I w i t h r a d i u s y t o u c h A B , A C a n d B C a t M , N a n d R r e s p e c t i v e l y . G i v e n t h a t B C = 1 + x , b y p r o p e r t i e s o f i s o s . t r i a n g l e , w e h a v e B R = R C = 2 1 + x B e s i d e s , b y t a n g e n t s f r o m e x t e r n a l p o i n t , w e h a v e B M = B R = 2 1 + x a n d A M = 1 − 2 1 + x = 2 1 − x C o n s i d e r △ A M I , u s i n g P y t h . T h e o r e m , w e h a v e y 2 + ( 2 1 − x ) 2 = x 2 ⋯ ⋯ ( 1 ) C o n s i d e r △ A R B , u s i n g P y t h . T h e o r e m , w e h a v e ( 2 1 + x ) 2 + ( x + y ) 2 = 1 ⋯ ⋯ ( 2 ) F r o m ( 1 ) a n d ( 2 ) , w e h a v e x 2 + 2 x − 1 = 0 I n △ A B C , A B 2 + A C 2 = 2 a n d B C 2 = ( 1 + x ) 2 = 1 + 2 x + x 2 B y c o n v e r s e o f P y t h T h e o r e m , t h e r e q u i r e d a n g l e i s 9 0 ∘ .
I thought of posting a solution, but Rohit Camfar's solution is exactly the same.
Huh?
No one actually got respect for the problem proposer. I know he just picked up a
r
i
g
h
t
Δ
A
B
C
and an
i
n
c
e
n
t
e
r
to find some results on
inscribed
and
circumscribed
figures and
f
o
r
t
u
n
a
t
e
l
y
got a simple result. But at least respect the
situation
.
K
.
I
.
P
.
K
.
I
.
G
.
C
o
n
s
t
: Produce
B
A
to
D
such that
B
D
=
B
I
. Join
D
C
and
I
C
.
Let
∠
A
B
C
=
2
θ
Now
A
B
=
B
C
=>
∠
A
=
9
0
−
θ
. =>
∠
B
I
C
=
9
0
+
a
n
g
l
e
A
/ 2 =
1
3
5
-
θ
/
2
But also,
A
B
+
A
I
=
B
D
=
B
C
. =>
∠
D
=
4
5
+
θ
/
2
Then
B
D
C
I
is a cyclic quadrilateral.
Also,
∠
A
D
I
=
θ
/
2
=>
∠
C
D
I
=
4
5
+
θ
/
2
-
θ
/
2
=
4
5
.
But Since
B
D
C
I
is cyclic.
∠
C
A
I
=
∠
C
D
I
=
4
5
. =>
∠
A
= 90
d
e
g
r
e
e
s
.
Problem Loading...
Note Loading...
Set Loading...
Motivation : Since we have been asked to find the value of an angle we will focus on angles and not sides.The first thing that comes to mind is the sine-rule.So we use that, In triangle ABC,we have, sin A B C = sin B A B ⟹ A B B C = sin B sin A .Let us keep that aside for now,and focus on the piece of information given to us, B C = A B + A I ⟹ A B B C = 1 + A B A I ,we have divided by A B since we know A B B C in terms of angles,now,if we can find the value of A B A I in terms of angles we can have an equation in terms of angles.Now,how do we find the value of A B A I ,that is the question.That can also be done with the help of sine-rule!just join B and I and apply it in the △ A B I we have, A B A I = cos 2 C sin 2 B = tan 2 B ,now,substituting all the values in the equation we get, sin B sin A = 1 + tan 2 B .Now,it would certainly be easier if the equation had just one variable which we can do by substituting 1 8 0 ∘ − 2 B = A ⟹ sin A = sin 2 B = 2 sin B cos B ,hence we have, 2 cos B = 1 + tan 2 B ,now,let us try and convert cos B into tan 2 B ,we have, tan 2 2 B = 1 + cos B 1 − cos B Applying componendo and dividendo we have, ( 1 − tan 2 B ) ( 1 + tan 2 B ) 1 + tan 2 2 B = cos B 1 ⟹ ( 1 − tan 2 B ) ( 2 cos B ) 1 + tan 2 2 B = cos B 1 ⟹ 1 + tan 2 2 B = 2 − 2 ( tan 2 B ) ⟹ 2 ( tan 2 B ) = 1 − tan 2 2 B ⟹ tan B = 1 ! ⟹ ∠ B = 4 5 ∘ ⟹ ∠ A = 9 0 ∘ .And done!